Interpretasi Atom dalam Kajian Surat Aż-Żāriyāt - Intan Masruroh Swastika (Lembaga Pengembangan Kinerja Dosen, 2023)
This research was conducted as an effort to obtain a reading material related to thermodynamics so that it can be more easily understood by students or other readers. In conducting research, a researcher needs to follow the rules and regulations that apply so that the results obtained can be said to be valid. This research was conducted using the literature review method, namely by looking for sources that lead to a literature review of the basic concepts of thermodynamics which in this search are very important and much needed. The results of this study are that there are implications or connectedness between the concept of a single particle system and thermodynamics. Single particle systems trapped in a potential well can be explained or understood from a thermodynamic perspective.